Transforming the Quality of Regional Civil Servants Through Innovative Training Programmes - Muttaqin, Muttaqin; Rizal, A. (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study employs a mixed-methods approach with an exploratory sequential design, aiming to analyze the effectiveness of innovative training programs for civil servants in Makassar City. The research was conducted in three government agencies: the Makassar City Civil Service and Human Resource Development Agency (BKPSDM), the Education Office, and the Health Office. The population consisted of all civil servants participating in the training programs in 2023 (n = 250). A purposive sampling technique was used, resulting in 50 respondents for the quantitative survey and 12 key informants for in-depth interviews. The data included pre- and post-training competency scores, participant satisfaction questionnaires, semi-structured interviews, and training program documents. Data were collected through questionnaires, interviews, and document review. Quantitative data were analyzed using descriptive statistics (mean, percentage, and competency score changes), while qualitative data were analyzed through thematic analysis, involving coding, theme categorization, and interpretation. Data triangulation was applied to ensure the validity and reliability of the findings. This methodology provides a comprehensive understanding of the implementation and impact of innovative training programs on the competencies and performance of civil servants in Makassar City.